1996
DOI: 10.1037/0278-6133.15.5.355
|View full text |Cite
|
Sign up to set email alerts
|

Validation of susceptibility as a predictor of which adolescents take up smoking in the United States.

Abstract: Smoking onset has 4 levels, with a "susceptibility" level preceding early experimentation. This study assessed the predictive validity of smoking susceptibility in a longitudinal study of a nationally representative sample of 4,500 adolescents who at baseline reported never having puffed on a cigarette. At follow-up 4 years later, 40% of the sample had experimented with smoking, and 8% had established a smoking habit. Baseline susceptibility to smoking, defined as the absence of a firm decision not to smoke, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
857
2
9

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 928 publications
(887 citation statements)
references
References 24 publications
19
857
2
9
Order By: Relevance
“…Therefore, to increase the power of our analyses we combined data for large and small retailers. Our findings are all based on self‐reported exposure and outcome data, and hence relatively open to error and bias; however, where possible we used measures that have previously been widely used and validated 10, 13, 27. Objective validation of exposure and outcome data was not feasible with the time and resources available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, to increase the power of our analyses we combined data for large and small retailers. Our findings are all based on self‐reported exposure and outcome data, and hence relatively open to error and bias; however, where possible we used measures that have previously been widely used and validated 10, 13, 27. Objective validation of exposure and outcome data was not feasible with the time and resources available.…”
Section: Discussionmentioning
confidence: 99%
“…Most smokers take up smoking during adolescence. Susceptibility to smoking, defined as absence of a firm decision not to smoke 12, has been shown to be a strong marker of experimentation with and uptake of smoking among adolescents 13, 14. There is also evidence that exposure to tobacco advertising increases susceptibility to smoking 12, and therefore potentially smoking uptake.…”
Section: Introductionmentioning
confidence: 99%
“…The few published studies generally divide nonusers into two subcategories, which we have termed resolute and vulnerable (Crano et al 2007), although specific terminology varies (Anderson et al 2002;Pierce et al 1996). Vulnerable nonusers have not used the substance, but are expected to do so.…”
mentioning
confidence: 99%
“…In research on tobacco, participants usually are asked a series of questions about smoking intentions. Those answering "definitely no" to all intent items are considered resolute, and are predicted not to initiate use; those who respond in any other way are considered vulnerable (Pierce et al 1996). The predictive validity of this measurement approach has not been tested in research on marijuana, and would seem a necessary first step in developing evidence-based prevention approaches.…”
mentioning
confidence: 99%
“…Data from California showed that risk based on both experimentation and willingness to consider smoking in the future may be applicable in low and middle-income countries [15]. Studies from South Africa and Argentina reveal the contributions of regional tobacco use patterns.…”
mentioning
confidence: 99%